Relationship between somatic maturation and physical performance with competitive trend in young football players - Soares, Delgivan Santos (2016)
In recent years, football has shown an increasing demand of players in training process, which is directly reflected in greater demand in the training of young athletes seeking high yield. In this context, physical, technical and psychological aspects directly influence the formation and performance of these athletes. The aim of the study was to examine the relationship between competitive trend with somatic maturation and physical performance in youth football players. The sample consisted of 86 soccer players, male, aged 13-17 years, from the training clubs in Londrina, Paraná. Anthropometric measurements of weight, height and sitting height were obtained. Somatic maturation was estimated by the age of peak height velocity (APHV) and tests for muscle power of the lower limbs, aerobic performance, abdominal muscle strength, and velocity and fatigue index were performed. The perception of competitive trends was obtained by the instrument evaluation system (ACS-2). No difference was observed in the indicators of competitive trend among categories (p> 0.05). The under-15, APHV and 7-sprints test showed a relationship with competitive tendency to beat (r = 0.30; p = 0.04 and r = 0.49; p = 0.009). On the other hand, in the under-17 only vertical jump (CMJ) was associated with a tendency to establish the competitive targets (r = 0.39; p = 0.01). It is concluded that no relationship was observed between competitive trend with indicators of maturity and physical performance, except for APHV and 7-sprint the under-15 and vertical jump in under-17.